TEACHER CAREER DEVELOPMENT IN EUROPEAN COUNTRIES AND ITS CONSISTENCY WITH TEACHER COMPETENCE FRAMEWORK (Comparative Professional Pedagogy, 2021)
The paper considers prospects of teacher career development in European countries, such as Poland, Italy, Spain, Slovenia, Greece, Hungary, Latvia, Lithuania, Sweden, Germany, Belgium and others. Main stages of career development and the role of teacher competence framework in this process have been characterized. Two types of teacher career development schemes in European countries – single (flat) and multi-level (hierarchical) – have been defined. It has been determined that teacher career promotion is only possible to stages that presuppose teaching. Requirements to teacher promotion to higher career stages are based on 6 criteria: positive evaluation; length of professional experience; demonstration of specific competences; specific professional development; research activities; running or designing professional development courses. The role of school administration and higher educational authorities (local and national) in decision making concerning teacher promotion in different European countries has been outlined. To get career promotion teachers can take on pedagogical or methodological responsibilities and roles outside classroom that can be diverse and related to subjects and curricula; student support; school life; teacher professional development; evaluation of teachers from other schools. It has been defined that in some countries, teachers are provided with career assistance that is the provision of information, coaching and counseling. Opportunities for teachers to extend their professional development and to get promotion to higher career steps have been analyzed. The key factor in decision making concerning teacher career promotion is teacher competence framework. It defines the fields of teacher competences. Some of these fields are common for all the frameworks but can be described in a different manner. As a rule, here belong psychological and pedagogical competences, subject knowledge and teaching approaches, organization of learning and assessment, innovative teaching approaches, communication with students, cooperation with colleagues, relations with parents and other stakeholders. Information in TCF is classified according to 4 categories: 1) initial teacher education; 2) introduction to the profession; 3) continuous professional development; 4) other.
Keywords: teacher competence framework; teacher career development; promotion; professional development; European countries; teacher evaluation/appraisal